Analysis of the Influence of Role Stress on Reduced Audit Quality - Pikar Setiawan, Angela Isabel Elinda, Sri Iswati, (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
Reduced Audit Quality is an act of decreasing audit quality that is considered to be a deliberate practice because it reduces the quality of audit work and thereby increasing the possibility of opinion on inappropriate financial statements. Factors affecting reduced audit quality actions arise due to the presence of role conflict, role ambiguity and role overload. This study was conducted to find out the effect of role conflict, role ambiguity, and role overload on reduced audit quality. The sampling was conducted using purposive sampling technique. The number of samples obtained was 44 samples. Data were collected using a questionnaire method via Google Forms on auditors working at public accounting firms in the city of Surabaya and Sidoarjo. Data analysis technique used for hypothesis testing was multiple linear regression analysis. The results of hypothesis testing show that role conflict and role ambiguity have no significant effect on reduced audit quality, but role overload has a significant effect on reduced audit quality.